A pharmacist check of patients' infection-related condition prior to drug preparation reduces anticancer drug wastage after mixing: a retrospective study - Hirotsugu Yamada; Yuto Yamada; Hirotoshi Iihara; Ryo Kobayashi; Hiroyuki Tanaka; Akio Suzuki (Taylor & Francis Group, 2023)
Abstract Background We previously reported that a standardized pharmacist check of medical orders related to the administration criteria of anticancer drugs prior to preparation of injectable anticancer drugs was useful for reducing drug wastage after mixing. To further reduce anticancer drug wastage after preparation, we added a pharmacist check of patients' infection-related condition to the previous protocol and assessed the effectiveness of the modified protocol for reducing injectable anticancer drug wastage. Methods In addition to the administration criteria of anticancer drugs, patients' infection-related condition, which was based on a body temperature ≥ 37.5 °C or elevated C-reactive protein (CRP) or white blood cell (WBC) count from baseline, was added to pharmacists' checklist of items used previously to prepare injectable anticancer drugs. We retrospectively compared the number, type and cost of anticancer drugs discarded after preparation and the reasons for discarding these drugs between pre- and post-protocol modification. Results The rate at which anticancer drugs were discarded after preparation was significantly reduced after introducing the modified protocol compared to the original protocol (0.288% [18/6253] vs. 0.095% [6/6331], P = 0.013). Furthermore, the number of cases for which mixed anticancer agents were discarded because of infection decreased from 11 (fever: n = 8; elevated CRP or WBC: n = 3) to one (elevated CRP: n = 1) a year. Conclusions In addition to the standard administration criteria of anticancer drugs, checking patients' infection-related condition, defined by a body temperature ≥ 37.5 °C or elevated CRP or WBC from baseline, before mixing by the pharmacist is useful for reducing anticancer drug wastage after preparation.